2022
DOI: 10.3390/ijms232415920
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Tool for the Analysis and Detection of Copy Number Variants Associated with Haemoglobinopathies

Abstract: Several types of haemoglobinopathies are caused by copy number variants (CNVs). While diagnosis is often based on haematological and biochemical parameters, a definitive diagnosis requires molecular DNA analysis. In some cases, the molecular characterisation of large deletions/duplications is challenging and inconclusive and often requires the use of specific diagnostic procedures, such as multiplex ligation-dependent probe amplification (MLPA). Herein, we collected and comprehensively analysed all known CNVs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…First, we investigate phenotypic differences in deletional hereditary persistence of fetal hemoglobin (HPFH) and δβ‐thalassemia, two molecularly similar conditions characterized by elevated fetal hemoglobin (Hb F) levels. In heterozygotes, their diagnosis is challenging as it strongly depends on hematological indices and empirical differences in the Hb F levels 15 . Using case‐level data stored in IthaPhen, we performed a series of logistic regression models (http://links.lww.com/HS/A441) to demonstrate a quantitative approach in the diagnosis of the 2 conditions.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…First, we investigate phenotypic differences in deletional hereditary persistence of fetal hemoglobin (HPFH) and δβ‐thalassemia, two molecularly similar conditions characterized by elevated fetal hemoglobin (Hb F) levels. In heterozygotes, their diagnosis is challenging as it strongly depends on hematological indices and empirical differences in the Hb F levels 15 . Using case‐level data stored in IthaPhen, we performed a series of logistic regression models (http://links.lww.com/HS/A441) to demonstrate a quantitative approach in the diagnosis of the 2 conditions.…”
Section: Figurementioning
confidence: 99%
“…In heterozygotes, their diagnosis is challenging as it strongly depends on hematological indices and empirical differences in the Hb F levels. 15 Using case-level data stored in IthaPhen, we performed a series of logistic regression models (Suppl. File 2) to demonstrate a quantitative approach in the diagnosis of the 2 conditions.…”
mentioning
confidence: 99%
“…At present, the thalassemia carrier screening strategy in China mainly focus on 23 most common variants, which include three deletions (--SEA , -α 4.2 , -α 3.7 ), three SNVs in HBA1/2, and 17 SNVs/indels in HBB (He et al, 2014). In clinical study, occasionally the genotypes identified by conventional PCR-based methods are not well correlated well with the phenotypes, indicating the possibility of rare variations, which are beyond the detecting range of conventional methods (Aliyeva et al, 2018;Minaidou et al, 2022).…”
Section: Introductionmentioning
confidence: 99%